Aging and Care and Management of Geriatric Pets - Kar, Payel; Rajesh, J. B.; Das, Manas; Marwein, Sherry Carelyne; Rose, Kh. Thanila; Debbarma, Jashima; Christen, C.; Lucy, Elone; Debnath, Ankita; Kumar, Nitin (International Journal of Bio-resource and Stress Management, 2026)
Aging is a normal biological process that affects all beings and is directly linked to longevity and age-related illnesses. It includes changes that are molecular, cellular, and organ-specific. As an animal ages, its organ systems degenerate, leading to a general decline in organ system function. One of the most significant risk factors for a variety of diseases, disabilities, and deaths in elderly pets is biological aging. The immune system, kidneys, digestive tract, and other organs are all gradually losing their ability to operate. The cardiovascular, renal, hepatic, musculoskeletal, ocular, and auditory systems are among the systems that are affected by aging. In older animals, a thorough check up that includes a blood test may identify a number of subclinical conditions that might be corrected with dietary changes. Anaemia, hypoalbuminemia, hypokalemia, elevated serum creatinine, or hyperglycemia in elderly pets may be signs of a number of diseases that can be treated with dietary changes as part of the care process. These conditions can be identified by routine haemato-biochemical testing. A thorough physical examination combined with a haemato-biochemical profile may reveal a number of age-related illnesses that can be treated early to prolong an animal’s lifespan and lessen the effects of aging, this could be controlled early on and reduce the negative consequences of aging on animals, extending their longevity.